2014
DOI: 10.5846/stxb201304040603
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of mining on landscape pattern and primary productivity in the grassland of Inner Mongolia: a case study of Heidaigou open pit coal mining

Abstract: Coal has been the primary energy resource that made rapid economic and social development in China possible. Yet, its extraction in the form of open鄄field mining operations changed landscape patterns considerably and created a suite of environmental and ecological problems. Therefore, it is very important to understand these landscape pattern dynamics and their effects on ecosystem processes. While open pit coal mining is one of the fast growing human modifications of the Earth忆 s surface which transforms land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that mining activities have a regular character in terms of the contribution of landscape ecological functions in mining areas. Kang et al (2014) considered the theoretical reference range for the impacts of the Shengli surface mine on the ecological health of grassland landscapes to be 5 km. Wu et al (2020) proposed that the mean values of a carbon density buffer zone from a mining landscape of 0-7 km belong to sensitive areas, which is in line with this study .…”
Section: Trends In Changes Of the Contribution Rate Of Landscape Ecol...mentioning
confidence: 99%
“…Previous studies have demonstrated that mining activities have a regular character in terms of the contribution of landscape ecological functions in mining areas. Kang et al (2014) considered the theoretical reference range for the impacts of the Shengli surface mine on the ecological health of grassland landscapes to be 5 km. Wu et al (2020) proposed that the mean values of a carbon density buffer zone from a mining landscape of 0-7 km belong to sensitive areas, which is in line with this study .…”
Section: Trends In Changes Of the Contribution Rate Of Landscape Ecol...mentioning
confidence: 99%
“…The landscape types at the mine scale were more complex, the land use type classification was subject to greater human influence, and the ecological and environmental conditions of certain landscape types, such as the waste dumps, were polarized, so the changes in its landscape index could not be linked to changes in the ecological environment. (3) Third, the calculation of the landscape index was affected by the spatial granularity and magnitude of the study and the quality of the remote sensing data and different data processing methods, which resulted in errors in the data [52]. However, there was a correlation between the change in landscape percentages of industrial and mining land types at the individual level, such as open-pit mining, and the quality of the regional ecological environment.…”
Section: The Ecological Evaluation Of Mines Through Analyzing Landsca...mentioning
confidence: 99%
“…However, the correlation between the landscape pattern changes and the ecosystem quality was not significant. However, a large number of studies at the landscape level in recent years have shown that it is closely related to ecosystem structure, function, and stability [52]. Some scholars believe that the intensification of anthropogenic activities promotes the development of landscape fragmentation and affects the energy flow and nutrient cycling in natural systems, leading to the reduction of ecosystem productivity and the loss of ecosystem functional stability.…”
Section: The Ecological Evaluation Of Mines Through Analyzing Landsca...mentioning
confidence: 99%
“…The groundwater is polluted, and ecological structure components are destroyed. This seriously affects the landscape structure and ecosystem of the mining area, destroys the ecological function of the landscape, and increases the ecological risks [30][31][32]. At the same time, due to the special location of "mines in the city", the dramatic changes in the landscape structure and ecological risk changes in the mining area and its surrounding areas seriously affect the daily life of residents in urban areas near the mining area [33].…”
Section: Introductionmentioning
confidence: 99%